Gifted Students' Reasons for Participating in Waste Management Themed Nature Education and Post-Training Views - Ceylan, Ozge; Aslan, Zeynep (ANKARA UNIV, FAC EDUCATIONAL SCIENCES, 2021)
Introduction: Nature education and science camps, which are out-of-school learning environments, offer the opportunity to prepare enriched programs for gifted students. This study supported by Turkey Scientific and Technological Research Council of Turkey (TUBITAK), it is aimed to examine the reasons gifted students participate in waste management themed nature education and their opinions about education. Method: The method of the study is a case study which is one of the qualitative research methods. The study group consists of 29 5th to 6th grade gifted students enrolled in science and art centers (SACs) in Istanbul. Students' views about the project that lasted for 5 days in June 2019 were analyzed using content analysis. The data were collected through the application form and project evaluation form prepared by the researchers, and the diaries were collected from the participants. Findings: Findings showed that students mostly participated in the project because of their knowledge, development of various skills and love for nature. At the beginning of the project, the students' level of knowledge about waste management was basic and intermediate. Also, they had positive opinions about the project, gained high-level knowledge about waste management, developed thinking skills, reached social and emotional satisfaction, and gained environmental awareness. Discussion: It was seen findings of previous research are consistent with those in the current study. This research can contribute to the preparation phase of out-of-school education and nature education practices and similar projects for gifted students.
Keywords: Waste management; recycling; gifted; nature education; TUBITAK; PERCEPTIONS; Education & Educational Research